HOW TO THE DEVELOPMENT STRATEGY OF SERBIA? - Popov, Đorđe (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Experiences, especially those countries that in their development have achieved results above average confirmed the need for preparing and implementation the development strategy for Serbia. Preparation of strategy requires an intellectual effort. It requires the collection, analysis and evaluation of a series of data and trends in the country and in the world. Before starting work on the strategy there is a need to formulate what can be considered as a strategy. Serbia has a total of 120 strategies. It could not be just each document, regardless of title ,is a strategy. Development of the strategy must be delegated to the experts who are not compromised with actively participation in the destruction of the Serbian economy in the past decade. The strategy should clearly define the desired model of the economy. The strategy must be focused on the primary goal: growing production and employment. Serbia must re-developed the industry. Foreign investments are important, but they can not substitute investments from domestic sources. Quality education, production and quality and uncorrupted public administration are the basic prerequisites for the successful economic development.